2021
DOI: 10.1002/rth2.12465
|View full text |Cite
|
Sign up to set email alerts
|

The role of platelets in sepsis

Abstract: A State of the Art lecture titled “The role of platelets in sepsis” was presented at the ISTH congress in 2020. Sepsis is a life‐threatening organ dysfunction caused by a dysregulated and multifaceted host response to infection. Platelets play a significant role in the coordinated immune response to infection and therefore in the inflammation and coagulation dysfunction that contributes to organ damage in sepsis. Thrombocytopenia has a high incidence in sepsis, and it is a marker of poor prognosis. The genesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 91 publications
1
27
0
Order By: Relevance
“…Platelets contribute to the dysregulated inflammatory response in ARDS [ 7 ] and sepsis [ 8 ]. Platelets are important innate immune cells and key mediators of hemostasis and thrombosis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Platelets contribute to the dysregulated inflammatory response in ARDS [ 7 ] and sepsis [ 8 ]. Platelets are important innate immune cells and key mediators of hemostasis and thrombosis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Platelet activation and aggregation by the bacteria may contribute to platelet depletion during invasive S. pyogenes infection. Thrombocytopenia, a low platelet count, occurs in sepsis and correlates with pathogenesis and severity of disease ( 45 ). We have previously reported that platelet activation, platelet-neutrophil complex formation, and thrombocytopenia occur in a mouse model of S. pyogenes serotype emm 1 sepsis ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Platelets play an important role in the coordinated immune response to an infection; however, during a dysregulated host response such as sepsis, platelet activation can cause inflammatory dysfunction and contribute to organ damage [ 27 ]. A previous study reported that a sharp drop in the serum albumin level due to bacteremia seriously affected the prognosis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%